Bibliometric Analysis of Medical Professionals' Professionalism on Healthcare Service Quality: A Study Using VOSviewer - Rizka Nurvianie; Sri Sundari (Postgraduate, University of Mataram, 2024)
Bibliometric analysis is a method used to describe various scientific publications (Tupan et al., 2016). This study employs bibliometric analysis on several Scopus-indexed articles discussing the topic of medical professionalism and its impact on healthcare service quality, using VOSviewer software. The aim of the bibliometric analysis in this research is to understand the development of the topic, publication trends, statistics across different countries, and subject areas related to medical professionalism and healthcare service quality from 2016 to 2023. Data were retrieved from the Scopus database using the keywords